Soluble thrombomodulin in bronchoalveolar lavage fluid is an independent predictor of severe drug‐induced lung injury. Issue 4 (15th December 2016) - Suzuki, Atsushi; Taniguchi, Hiroyuki; Kondoh, Yasuhiro; Ando, Masahiko; Watanabe, Naohiro; Kimura, Tomoki; Kataoka, Kensuke; Yokoyama, Toshiki; Sakamoto, Koji; Hasegawa, Yoshinori
ABSTRACT: Background and objective: Drug‐induced lung injury (DLI) can result from a vast number of agents, and sometimes presents findings similar to those of acute respiratory distress syndrome (ARDS). Previous studies have reported that circulating levels of soluble thrombomodulin (TM) reflect endothelial injuries, which play key roles in the development of ARDS. We hypothesized that endothelial injuries are an important aspect of pathogenesis in severe DLI. The primary aim of this study was to examine the associations between soluble TM and disease severity in DLI patients. Methods: Of the 2580 patients who underwent a bronchoalveolar lavage (BAL) procedure at Tosei General Hospital between May 2007 and February 2015, we retrospectively analysed the data of 68 DLI patients. Soluble TM in plasma and BAL fluid (BALF), and other biomarkers were included in our analysis. Results: At the time of diagnosis, 39 patients (57%) had respiratory failure (partial pressure of oxygen/inspiratory oxygen fraction ratio, PaO2 /FiO2 ratio < 300). There was a significant negative linear correlation between the PaO2 /FiO2 ratio and soluble TM in BALF (r = −0.448, P  < 0.001). In a stepwise multiple regression analysis, soluble TM in BALF and surfactant protein D (SP‐D) were the only independent determinants of the PaO2 /FiO2 ratio. Additionally, in a multivariate logistic regression model, soluble TM in BALF (adjusted OR (aOR): 7.48, 95% CI: 1.60–34.98) and SP‐D (aOR: 5.31, 95% CI: 1.40–20.15) was an independent predictor of respiratory failure (PaO2 /FiO2 ratio < 300). Conclusion: Soluble TM in BALF is an independent predictor of severe DLI. These findings underscore the importance of pulmonary endothelial injuries in the pathogenesis of severe DLI. Abstract : Soluble thrombomodulin in bronchoalveolar lavage is an independent predictor of severe drug‐induced lung injury (DLI). Pulmonary endothelial injuries are an important aspect of pathogenesis in severe DLI.